Metalloproteinases in disease: identification of biomarkers of tissue damage through proteomics. (2nd December 2018) - Herrera, Cristina; Escalante, Teresa; Rucavado, Alexandra; Fox, Jay W.; Gutiérrez, José María
ABSTRACT: Introduction : Metalloproteinases play key roles in health and disease, by generating novel proteoforms with variable structure and function. Areas covered : This review focuses on the role of endogenous [a Disintegrin and Metalloproteinase (ADAMs), ADAMs with thrombospondin motifs (ADAMTS), and matrix metalloproteinases (MMPs)] and exogenous metalloproteinases in various disease conditions, and describes the application of mass spectrometry-based proteomics to detect qualitative and quantitative changes in protein profiles in tissues and body fluids in disease. Emphasis is placed on the proteomic analysis of exudates collected from affected tissues, including methods that enrich newly generated protein fragments derived from proteolysis in cells, stroma, or extracellular matrix. The use of proteomic analysis of exudates in the study of the local tissue damage induced by metalloproteinases derived from viperid snake venoms is discussed, particularly in relation to extracellular matrix degradation and to the overall pathology of these envenomings. Expert commentary : The information provided by these proteomics approaches is paving the way for the identification of biomarkers based on particular proteolytic signatures associated with different pathologies. Together with other methodological approaches, a comprehensive view of the mechanisms and dynamics of diseases can be achieved. Such basis of knowledge allows for the design of novel diagnostic and therapeutic approaches within the frame of 'precision' or 'personalized' medicine.